Review of ASP Flooding - Majidaie, Saeed (2010)
The ASP has been found to be one of the major EOR techniques that can be successfully used in producing light and medium oils left in reservoirs after primary and secondary recovery. This study is a review of the ASP field experience as it is found in the literature today. For the fields reviewed, a common trend for the successful injections is an increased oil recovery in the range of 15 OOIP to 30% OOIP of the residual oil. Mechanisms of ASP flooding, Laboratory work requirements for ASP flooding, surface facility requirements for ASP flooding, and ASP project performance are reviewed.